Granulocyte Colony-Stimulating Factor Effectively Mobilizes TCR γδ and NK Cells Providing an Allograft Potentially Enhanced for the Graft-Versus-Leukemia Effect for Allogeneic Stem Cell Transplantation - Minculescu, Lia; Sengelov, Henrik; Marquart, Hanne Vibeke; Ryder, Lars Peter; Fischer-Nielsen, Anne; Haastrup, Eva (Frontiers in Immunology, 2021)
Allogeneic hematopoietic stem cell transplantation (HSCT) is a potential cure for patients with hematological malignancies but substantial risks of recurrence of the malignant disease remain. TCR γδ and NK cells are perceived as potent innate effector cells in HSCT and have been associated with post-transplant protection from relapse in clinical studies. Immunocompetent cells from the donor are crucial for patient outcomes and peripheral blood stem cells (PBSC) are being increasingly applied as graft source. G-CSF is the preferential mobilizing agent in healthy donors for PBSC grafts, yet effects of G-CSF on TCR γδ and NK cells are scarcely uncovered and could influence the graft composition and potency of these cells. Therefore, we analyzed T and NK cell subsets and activation markers in peripheral blood samples of 49 donors before and after G-CSF mobilization and - for a subset of donors -also in the corresponding graft samples using multicolor flowcytometry with staining for CD3, CD4, CD8, TCRαβ, TCRγδ, Vδ1, Vδ2 , HLA-DR, CD45RA, CD197, CD45RO, HLA-DR, CD16, CD56 and CD314. We found that TCR γδ cells were mobilized and harvested with an efficiency corresponding that of TCR αβ cells. For TCR γδ as well as for TCR αβ cells, G-CSF preferentially mobilized naïve and terminally differentiated effector (TEMRA) cells over memory cells. In the TCR γδ cell compartment, G-CSF preferentially mobilized cells of the nonVδ2 types and increased the fraction of HLA-DR positive TCR γδ cells. For NK cells, mobilization by G-CSF was increased compared to that of T cells, yet NK cells appeared to be less efficiently harvested than T cells. In the NK cell compartment, G-CSF-stimulation preserved the proportion of CD56dim NK effector cells which have been associated with relapse protection. The expression of the activating receptor NKG2D implied in anti-leukemic responses, was significantly increased in both CD56dim and CD56bright NK cells after G-CSF stimulation. These results indicate differentiated mobilization and altering properties of G-CSF which could improve the effects of donor TCR γδ and NK cells in the processes of graft-versus-leukemia for relapse prevention after HSCT.